Wastewater reuse technology success. Issue 4 (July 2018) - Unknown
Abstract : To help alleviate water shortages, treated wastewater can be turned into high quality fresh water using cutting-edge technology with tight controls on the treatment process. To demonstrate its feasibility, a number of bodies in California initiated an indirect potable reuse project.